A rapid approach for predication and discrete lay-up optimization of glass fiber/polypropylene composite laminates under impact. (October 2015) - Alemi-Ardakani, M.; Milani, A.S.; Yannacopoulos, S.; Borazghi, H.
Abstract: Taguchi design of experiments is a much known statistical method for cost/time reduction during experimental investigation and quality engineering of complex systems and processes. In the present article, efficiency, accuracy, strengths and limitations of this method in predicting and discretely optimizing impact response of FRP composites have been studied through a case study on polypropylene/E-glass laminates with unidirectional, plain, and twill weave architectures. In parallel, drop weight impact tests, X-ray micro-tomography, and pre- and post-impact four-point flexural testing are employed for two purposes: (a) gaining further knowledge on induced impact damage mechanisms, and (b) further assessment and verification of the Taguchi results. In spite of the fact that impact events of the FRP laminates are highly nonlinear and accompany high level of uncertainty, it was found that this design of experiments method is capable of predicting and maximizing the absorbed impact energy with a reduced number of runs and reasonable error. Finally, by correlating macro-level predictions to micro-level damage observations via X-ray tomography, the underlying assumptions of the method were further scrutinized, and in particular it was found that the plies interaction effect is not a limiting factor in predicting the total absorbed energy of the laminates. Overall, the experimental time/cost saving in the performed impact optimization case study was over 50% using the Taguchi L9 orthogonal array. Highlights: It is shown how fractional factorial DOE methods can be employed for predicting and optimizing impact response of FRPs. Cost/time saving via Taguchi DOE implementation was in the order of 66% in the performed case study. Energy absorption results are correlated to micro-tomographic, pre- and post-impact bending tests. Contribution percentage of each laminate ply/fabric architecture on the impact response is identified.